The effectiveness of wordwall application in enhancing student interest in learning among phase e-learners on the topic of three-variable linear equation systems - Nailani, Hunafa; Rezeki, Sri (Institute of Computer Science (IOCS), 2024)
The aim of this research is to determine the effectiveness of using the Wordwall application to enhance the learning interest of Phase E students in mathematics, specifically on the topic of three-variable linear equation systems, at YLPI High School in Pekanbaru, and the effectiveness of using the Wordwall application in closing activities as assessed through Post-non-test results. The research employed an experimental design with a quantitative descriptive data collection technique. The research subjects were students of class X.1 and X.2 at YLPI High School in Pekanbaru. Data collection techniques included: (1) Questionnaires, (2) Observation Sheets, and (3) Documentation. The results of this study are as follows: (1) In the second post-non-test, the average learning interest of the experimental class was 89, while the average learning interest of the control class was 85.3. (2) Based on the calculation results, ES (Effect Size) was 1.04, indicating that the effectiveness of learning interest falls within the high criteria.